2002
DOI: 10.3354/meps232291
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variation in foraging range and habitat of macaroni penguins Eudyptes chrysolophus at South Georgia

Abstract: In marine ecosystems, characterisation of the foraging areas and habitats of predators is a key factor in interpreting their ecological role. We studied the foraging areas of the macaroni penguin Eudyptes chrysolophus at Bird Island, South Georgia, throughout the breeding seasons of 1999 to 2001 using satellite tracking. We investigated differences in foraging ranges and characteristics between different stages of the breeding season, between sexes, between years and between individuals. During incubation, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 36 publications
4
57
0
Order By: Relevance
“…Although a decrease in penguin foraging range between the incubation and chick rearing stages of breeding is well documented , Barlow & Croxall 2002, variations in range post hatch are less consistent. Increasing foraging ranges as chick rearing progresses are reported for macaroni, royal and Adélie penguins at a number of locations , Watanuki et al 1999, Wienecke et al 2000, Barlow & Croxall 2002, Lynnes et al 2002, Kato et al 2003, Ainley et al 2004, including Béchervaise Island (this study) but apparently not at others (Lishman 1985, Trivelpiece et al 1987, Wienecke et al 2000.…”
Section: Partitioning Of Resources During Chick Rearing and Life Histmentioning
confidence: 99%
“…Although a decrease in penguin foraging range between the incubation and chick rearing stages of breeding is well documented , Barlow & Croxall 2002, variations in range post hatch are less consistent. Increasing foraging ranges as chick rearing progresses are reported for macaroni, royal and Adélie penguins at a number of locations , Watanuki et al 1999, Wienecke et al 2000, Barlow & Croxall 2002, Lynnes et al 2002, Kato et al 2003, Ainley et al 2004, including Béchervaise Island (this study) but apparently not at others (Lishman 1985, Trivelpiece et al 1987, Wienecke et al 2000.…”
Section: Partitioning Of Resources During Chick Rearing and Life Histmentioning
confidence: 99%
“…How can these behavioral changes be explained? Several studies on seabirds have shown that mass gain at sea is positively related to foraging trip duration (e.g., Weimerskirch 1995; Barlow and Croxall 2002;Emmerson et al 2011), because foraging trip lengths may vary depending on food availability and foraging success (e.g. , Cairns 1987;Williams 1995).…”
Section: Foraging Trip Durationmentioning
confidence: 99%
“…Breeding pairs with young chicks were then identified on nests during the predawn hours, when most females are in the colony and preparing to leave for foraging trips (Barlow and Croxall 2002), and both partners were marked with a small dab of colored water-based paint on their chests. Macaroni penguins are sexually size dimorphic (Williams 1995), allowing for accurate identification of paired individuals; thus, females were dabbed yellow and males blue to allow easy sex identification.…”
Section: Study Site and Field Sampling Protocolmentioning
confidence: 99%
“…More specifically, we frame our study as a test of the corticosterone-adaptation hypothesis (Bonier et al 2009a) using female macaroni penguins (Eudyptes chrysolophus) during the brood-guard stage of chick rearing as a model system. Macaroni penguins offer a particularly tractable model as females initiate multiple, consecutive foraging trips and are solely responsible for provisioning young chicks while males remain on the nest and sustain themselves through somatic energy reserves (Williams 1995;Barlow and Croxall 2002). Because females spend less time at the nest and are not principally responsible for chick brooding or guarding, this allows us to test the effect of corticosterone on foraging behavior and prolactin levels without the potentially confounding effect of long periods of food deprivation.…”
Section: Introductionmentioning
confidence: 99%